2016
DOI: 10.1111/medu.13131
|View full text |Cite
|
Sign up to set email alerts
|

How clinical medical students perceive others to influence their self-regulated learning

Abstract: ObjectivesUndergraduate medical students are prone to struggle with learning in clinical environments. One of the reasons may be that they are expected to self‐regulate their learning, which often turns out to be difficult. Students’ self‐regulated learning is an interactive process between person and context, making a supportive context imperative. From a socio‐cultural perspective, learning takes place in social practice, and therefore teachers and other hospital staff present are vital for students’ self‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 34 publications
7
60
0
4
Order By: Relevance
“…Such a need for relatedness has never been described in SRL theories, but makes sense when combined with self‐determination theory. In one of our studies on SRL in clinical contexts, the importance of relatedness and relationships for SRL was also evident . Just like SRL, relatedness is inextricably linked to context, because to have a sense of relatedness other people need to be present.…”
Section: Self‐regulated Lifelong Learning In Medical Educationmentioning
confidence: 71%
See 1 more Smart Citation
“…Such a need for relatedness has never been described in SRL theories, but makes sense when combined with self‐determination theory. In one of our studies on SRL in clinical contexts, the importance of relatedness and relationships for SRL was also evident . Just like SRL, relatedness is inextricably linked to context, because to have a sense of relatedness other people need to be present.…”
Section: Self‐regulated Lifelong Learning In Medical Educationmentioning
confidence: 71%
“…Therefore context includes what people do in a context, the roles that people have in a context, interpersonal relationships, and the physical context in which learners learn. This results in a context that is not static but rather flexible, emergent, dynamic and changing, and can be interpreted differently by individuals . This explains why learners in different contexts may engage in active learning very differently.…”
Section: Learning In Contextmentioning
confidence: 99%
“…Typically, learning goal programmes or individualised learning plans are examined in relation to how they help trainees develop into more self‐regulated lifelong learners, sometimes termed ‘master learners’ . Previous analyses of SRL have shown that the social environment provides important feedback and support for learners . However, these studies have not demonstrated how both learners’ and supervisors’ actions can change as they collaboratively seek to reconcile the challenges of work with learning goals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several investigations have found collaborative dialogue to be essential for successful implementation of ostensibly SRL educational interventions whether they be clerkship student learning goals or resident individualised learning plans . Berkhout et al . showed that as learners became more experienced in workplace learning, their pursuit of SRL became increasingly collaborative with supervisors.…”
mentioning
confidence: 99%